-x+188=-436+15x

Simple and best practice solution for -x+188=-436+15x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x+188=-436+15x equation:


Simplifying
-1x + 188 = -436 + 15x

Reorder the terms:
188 + -1x = -436 + 15x

Solving
188 + -1x = -436 + 15x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15x' to each side of the equation.
188 + -1x + -15x = -436 + 15x + -15x

Combine like terms: -1x + -15x = -16x
188 + -16x = -436 + 15x + -15x

Combine like terms: 15x + -15x = 0
188 + -16x = -436 + 0
188 + -16x = -436

Add '-188' to each side of the equation.
188 + -188 + -16x = -436 + -188

Combine like terms: 188 + -188 = 0
0 + -16x = -436 + -188
-16x = -436 + -188

Combine like terms: -436 + -188 = -624
-16x = -624

Divide each side by '-16'.
x = 39

Simplifying
x = 39

See similar equations:

| 4hsquared-2h(h-2)= | | 3tg^2(5x)-9=0 | | 10x-15=9x+3 | | =-14g-21+24g+16 | | 3n+10=n-7 | | =7(-2g-3)+8(3g-2) | | -12(-8x-39)=-588 | | 2m-55n7/14m6n3 | | 2.3x*3.2=-9.4 | | -3(y-2y)+4=-3(2y-y)+8+5y | | -5+55=55 | | 50+2g=7g | | 9x^2+3x+25=11 | | (x+2)(2x-3)=x+26 | | A=M(1+rt) | | http://mathsonline.com.au/assets/interactives/images/3244-116-2.png | | factor-16x^2+34x-18= | | 0.9x-0.1(10-2x)=-0.4(x-5) | | 10-8x=10x+1 | | 8-(-3x-2)= | | 8-(-3x-1)= | | x^2-3000x+1600=0 | | -17=14x-6/-12 | | -4*(5-x)+(3-x)*(4-x)*(5-X)-4*(3-X)=0 | | 3x-6(6x-15)=-9 | | 5+x=-10+7 | | -4(5-x)+(3-x)(4-x)(5-X)-4(3-X)=0 | | -3.3x=-29.7 | | -182=6x-4(3x+29) | | ft(-4)=3x^2+7 | | 3-2(2x-4)=3x-4 | | x+.15x=1500 |

Equations solver categories